La reconfiguración del mapa de la pobreza multidimensional en Chile: Un análisis comparativo de las carencias y brechas en los hogares rurales. (2018)
The objective of this article is to characterize their situation of poverty according to the metric of the Multidimensional perspective. Within the results, found that deficiencies are more pronounced in rural areas, and they become more acute when using multilevel indicators. From this focus, the indicators that showed the greatest precariousness and relevance in the configuration of rural poverty are education, work and housing. It is posed that despite economic precariousness and restricted access to goods and services, rural areas are a space where manifestations of solidarity and subjective well-being reach greater intensity with respect to the city. To conclude, notwithstanding the acknowledged limitations of the incipient multidimensional perspective, this new approach analytically diversifies and significantly contributes to the understanding and approach to poverty in Chile